PENGARUH DANA ZAKAT DAN ISLAMIC CORPORATE SOCIAL RESPONSIBILITY TERHADAP KINERJA KEUANGAN PERBANKAN SYARI’AH (PADA BANK DEVISA SYARIAH BERDASARKAN ISR INDEX) - Eko Setiawan; Yuliansyah Yuliansyah; Rindu Rika Gamayuni (Universitas Multimedia Nusantara, 2022)
Abstract - This study discusses banking that is engaged in services, therefore public trust is very important for smooth business, Islamic banking needs to be supported by good bank performance because if financial performance in this study is proxied by ROA and ROE which are reported to be good, it will add information for potential investors so that potential investors will invest their funds. The purpose of this study was to determine the effect of zakat funds and Islamic Corporate Social Responsibility on financial performance in Islamic foreign exchange banks. This study uses Islamic Foreign Exchange Banks as the research sample. The data used is the annual financial report of the Islamic Foreign Exchange Bank for the period 2011-2018 which was obtained from the official website of each bank. The sample used is 32 financial statements. The sampling technique uses a saturated sampling technique, namely the determination of the sample when all members of the population are used as samples. The hypothesis test carried out was the T test using spss v 20. The results showed that the data were normally distributed. The results of the coefficient of determination test showed that statistically the independent variables namely zakat and ICSR were able to explain the dependent variable ROA of 8.60% while the remaining 91.40% explained by other variables that were not included in this study while the ROE of 9.30% the remaining 90.70% was explained by other variables that were not included in this study. The results of the t-test of zakat funds and Islamic Corporate Social Responsibility have no effect on the financial performance of Islamic Foreign Exchange Banks. Keywords: Zakat Funds; Islamic Corporate Social Responsibility (ICSR); Return On Assets (ROA); Return On Equity (ROE)